Comparative influence of active mineral admixtures on the strength properties of fiber-reinforced reactive powder concrete - Bordiuzhenko, Oleh; Dvorkin, Leonid; Ribakov, Yuri (Archives of Civil Engineering, 2026)
The use of active mineral admixtures in concrete and reinforced concrete technology is one of the most important ways to save resources. Silica fume is one of this type’s most popular and effective admixtures. However, the use of silica fume is not always economically reasonable due to its high cost. The paper presents the results of comparative studies on the effect of various active mineral admixtures on the properties of reactive powder concrete (RPC) and fiber-reinforced powder concrete (FRPC). Five different admixtures were investigated: ground quartz sand, blast furnace slag, fly ash, metakaolin and silica fume. The highest strength values were achieved for RPC and FRPC containing microsilica and fly ash together with metakaolin. The RPC compositions containing fly ash and metakaolin achieved at 28 days an average compressive strength of approximately 125 MPa and a flexural strength of over 16 MPa. This is only an average of 10–20% less compared to concrete containing silica fume, however the cost of silica fume is about 2–3 times higher compared to fly ash and metakaolin. Thus, it becomes possible to replace high-cost silica fume with the proposed composite mineral admixture consisting of fly ash and metakaolin. Adding steel microfibers to the tested RPC compositions can increase compressive strength by 10–20%, depending on the composition. With a steel fiber consumption of 240 kg/m3, the flexural strength increases by 1.5 to 2.3 times, reaching 35 MPa.